Review: Stockmen from Tekoa, Sycomores from Sheba: A Study of Amos’ Occupations - Gillingham, Susan E. (The journal of theological studies, 2005)
Stockmen from Tekoa, Sycomores from Sheba: A Study of Amos’ Occupations Richard C. Steiner x + 158 (Catholic Biblical Quarterly Monograph Series, 36.)Washington, DC The Catholic Biblical Association of America 2003 0 915170 35 3 Paper$10.50